A cluster of acute flaccid paralysis and cranial nerve dysfunction temporally associated with an outbreak of enterovirus D68 in children in Colorado, USA. Issue 9978 (25th April 2015) - Messacar, Kevin; Schreiner, Teri L; Maloney, John A; Wallace, Adam; Ludke, Jan; Oberste, M Stephen; Nix, W Allan; Robinson, Christine C; Glodé, Mary P; Abzug, Mark J; Dominguez, Samuel R
Summary: Background: Clusters of acute flaccid paralysis or cranial nerve dysfunction in children are uncommon. We aimed to assess a cluster of children with acute flaccid paralysis and cranial nerve dysfunction geographically and temporally associated with an outbreak of enterovirus-D68 respiratory disease. Methods: We defined a case of neurological disease as any child admitted to Children's Hospital Colorado (Aurora, CO, USA) with acute flaccid paralysis with spinal-cord lesions involving mainly grey matter on imaging, or acute cranial nerve dysfunction with brainstem lesions on imaging, who had onset of neurological symptoms between Aug 1, 2014, and Oct 31, 2014. We used Poisson regression to assess whether the numbers of cases during the outbreak period were significantly greater than baseline case numbers from a historical control period (July 31, 2010, to July 31, 2014). Findings: 12 children met the case definition (median age 11·5 years [IQR 6·75–15]). All had a prodromal febrile illness preceding neurological symptoms by a median of 7 days (IQR 5·75–8). Neurological deficits included flaccid limb weakness (n=10; asymmetric n=7), bulbar weakness (n=6), and cranial nerve VI (n=3) and VII (n=2) dysfunction. Ten (83%) children had confluent, longitudinally extensive spinal-cord lesions of the central grey matter, with predominant anterior horn-cell involvement, and nine (75%) children had brainstem lesions. Ten (91%) of 11 children had cerebrospinal fluid pleocytosis. Nasopharyngeal specimens from eight (73%) of 11 children were positive for rhinovirus or enterovirus. Viruses from five (45%) of 11 children were typed as enterovirus D68. Enterovirus PCR of cerebrospinal fluid, blood, and rectal swabs, and tests for other causes, were negative. Improvement of cranial nerve dysfunction has been noted in three (30%) of ten children. All ten children with limb weakness have residual deficits. Interpretation: We report the first geographically and temporally defined cluster of acute flaccid paralysis and cranial nerve dysfunction in children associated with an outbreak of enterovirus-D68 respiratory illness. Our findings suggest the possibility of an association between enterovirus D68 and neurological disease in children. If enterovirus-D68 infections continue to happen in an endemic or epidemic pattern, development of effective antiviral or immunomodulatory therapies and vaccines should become scientific priorities. Funding: National Center for Advancing Translational Sciences, National Institutes of Health.